Protection of Families with Disabilities; A Juridical and Maqashid Shariah Analysis - Partiah, Siti; Bin Ali Samson, Umar Abdul Aziz; Subakti, Try (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
A disparity in service delivery persists for individuals and family with disabilities, hindering their equal access to rights under the law. Observational data from the 2024 elections reveals that many individuals with disabilities were disenfranchised due to factors such as inaccessible voting facilities, inadequate support from officials, and familial perceptions of them as a burden. This situation is at odds with existing legislation, which should prioritize family protection beyond mere formal recognition of human rights. This study examines legal protection for individuals with disabilities through the lens of Maqashid Shariah, utilizing a qualitative library research approach that analyzes relevant legislation, human rights principles, and Maqashid Shariah frameworks. The research findings highlight that Law Number 8 of 2016 provides legal safeguards for families with disabilities, guaranteeing fundamental rights such as life, education, and employment. These protections align with the five essential objectives of Maqashid Shariah, underscoring their relevance to both national and religious goals.